Prospects and organizational potential for post-war recovery and development of sports infrastructure in Ukraine - Kushnir, Volodymyr (Theory and Practice of Public Administration, 2025)
This study addresses the challenges and strategic perspectives of post-war recovery and development of sports infrastructure in Ukraine. The relevance of this research is determined by the extensive destruction caused by military aggression, with over 600 sports facilities destroyed and damages estimated at approximately $600 million. The purpose of the article is to conceptualize the prospects and potential for post-war recovery and development of sports infrastructure in Ukraine through a systematic analysis of public administration mechanisms and stakeholders. The research examines the legal framework governing sports infrastructure development and analyzes the potential contribution of various public administration entities, including the Ministry of Youth and Sports, Ministry of Health, regional state administrations, and local self-government bodies. The study reveals that while the political mechanism for sports infrastructure development is established at the state level, significant attention must be focused on economic, managerial, and organizational mechanisms to ensure effective implementation. The author proposes a strategic approach to recovery that encompasses distinct temporal phases. The initial phase (1-2 years) focuses on damage assessment, preservation of partially damaged facilities, and implementation of modular solutions for rapid restoration of basic infrastructure. The medium-term phase (2-5 years) emphasizes systematic reconstruction with elements of modernization and implementation of innovative financing models. The long-term phase (5-10 years) targets transformational development through the creation of integrated sports ecosystems, digital transformation of management, and formation of multifunctional clusters. The research substantiates the necessity of implementing innovative financing mechanisms, including enhanced public-private partnership models with integrated social obligations, decentralized financial instruments for sports facility tokenization, and smart contracts for transparent fund management. These approaches can effectively address the limitations of budgetary resources in the post-war period while ensuring broader access to sports infrastructure. The transformational potential of sports infrastructure recovery extends beyond the sports sphere itself, serving as a catalyst for broader social changes. The formation of integrated sports ecosystems optimizes resource utilization and enhances social impact through integration with educational institutions, healthcare systems, and rehabilitation centers. Furthermore, sports infrastructure can play a crucial role in the social reintegration of war-affected territories, fostering community cohesion and psychological recovery. The study concludes that a strategic approach to sports infrastructure recovery represents an integral component of Ukraine’s socio-economic reconstruction and transformation. Through effective coordination of public administration mechanisms with innovative approaches to financing, design, and management, sports infrastructure can serve as a powerful instrument for positive social change and sustainable development.